2021
DOI: 10.1038/s41430-021-00943-0
|View full text |Cite|
|
Sign up to set email alerts
|

Amino acid metabolism and signalling pathways: potential targets in the control of infection and immunity

Abstract: Defences to pathogens such as SarCoV2 in mammals involves interactions between immune functions and metabolic pathways to eradicate infection while preventing hyperinflammation. Amino acid metabolic pathways represent with other antimicrobial agent potential targets for therapeutic strategies. iNOS-mediated production of NO from Arg is involved in the innate inflammatory response to pathogens and NO overproduction can induce hyperinflammation. The two Arg-catabolising enzymes Arg1 and IDO1 reduce the hyperinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 82 publications
(93 reference statements)
1
38
0
Order By: Relevance
“…We have mentioned that it can be an immunity booster so the possibility of infection due to nCoV will be less. [ 19 , 37 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have mentioned that it can be an immunity booster so the possibility of infection due to nCoV will be less. [ 19 , 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…Even, amino-acids the units of the proteins and so produces the antibodies in human to fight against the infection from SARS-CoV-2. [ 19 , 20 ] In the present work, authors have performed the DFT calculations of amino-acids and then their promising role in the inhibition of main protease of SARS-CoV-2 was investigated using molecular docking and molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Itaconic acid is derived from activated macrophages and can inhibit inflammation at low doses but promote inflammatory apoptosis at high doses. 47 Thus, in the HC group, the balanced composition of commensal flora may lead to relative amino acid starvation in the airway that could restrict viral invasion 11 and may also inhibit excessive inflammation. Once dysbiosis occurs in the LRT, depletion or abnormal enrichment of commensal flora will cause the host's original balanced immune state to be disrupted, and metabolic reprogramming of immune cells may also occur, causing invasion of pathogens and then an excessive inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Human microbial communities are typically complex and involve interactions between immune functions and metabolic pathways to eradicate infection while preventing hyperinflammation. [9][10][11] In healthy individuals, the composition of the airway microbiota is diverse, well balanced, and may comprise Prevotella, Streptococcus, and Veillonella, accompanied by other dynamically changing colonizers. 12 Many studies have found significant differences in the composition of the lung microbiome during lung diseases 13 and these diseases are generally associated with a loss of bacterial diversity or the dominance of a small group of taxa.…”
Section: Introductionmentioning
confidence: 99%
“…43 Arginine is a substrate for nitric oxide production required for the innate inflammatory response. 74 It is also necessary for normal T lymphocyte function, 75 and is known to have anti-inflammatory properties. 76 Another important attribute of the anti-inflammatory response in females is supported by the presence of carnitine and glycerol in their serum.…”
Section: Discussionmentioning
confidence: 99%